Uptake of advance care planning and its circumstances: An nationwide survey in Australian general practice. (16th September 2021) - Ding, Jinfeng; Cook, Angus; Saunders, Christobel; Chua, David; Licqurish, Sharon; Mitchell, Geoffrey; Johnson, Claire E.
Abstract: There are potential benefits associated with advance care planning (ACP), and general practitioners (GPs) are well placed to coordinate ACP initiatives with their patients. Few studies have reported on the uptake of different forms of advance care plan conducted by GPs and how this affects patients' place of death. The primary aims of the study were to examine uptake of verbal (conversations regarding care preferences) and written (documented care preferences) advance care plans and their associated factors from the perspective of Australian GPs. The secondary aim was to determine the impact of different types of advance care plans on place of death. Sixty‐one GPs from three Australian states used a validated clinic‐based data collection process to report on care provided for decedents in the last year of life, including provision of services, place of death, and uptake of ACP. We found that 58 (27.9%), 91 (43.7%) and 59 (28.4%) reported decedents had no advance care plans, verbal plans or written plans, respectively. There were increased uptake of both verbal plans (relative risk ratio [RRR] = 13.10, 95% confidence interval [CI]: 2.18–77.34) and written plans (RRR = 10.61, 95% CI: 1.72–65.57) if GPs foresaw the death for >90 days versus <7 days. Palliative care training history for GPs predicted uptake of verbal plans (RRR = 5.83, 95% CI: 1.46–31.93). Patients with verbal plans versus no plans were more likely to die at a private residence (odds ratio = 4.97, 95% CI: 1.32–18.63). Our findings suggest that expectation of death for at least three months prior to the event (where clinically possible) and palliative care training for GPs improve the uptake of ACP in general practice. Larger pragmatic trials are required to determine the impact of ACP on patients' place of death.